Acrometastases to the hand in stomach carcinoma: a rare entity - Kumar, Ashok (BMJ Case Rep, 2019)
Acrometastasis caused by malignancy is a very rare phenomenon, and gastric malignancy metastasising to the hands is an even rarer entity. It accounts for only 0.1% of all metastatic osseous involvement, and may be a late manifestation of malignancy or may even be a presenting symptom. It is generally seen with lung primary, followed by kidney and breast, and less frequently with colon, liver, prostate, rectum and stomach primaries. The terminal phalanges are the most common sites of metastases, followed by the metacarpals and the proximal phalanges. We present a case of stomach carcinoma with metastases to the liver and adrenals which was managed with three lines of chemotherapy. He was lost to follow-up and reported after 1 year with swelling over his left hand, which was managed with palliative radiation to the hand in view of severe pain, followed by chemotherapy.